Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the recursive formula for the given sequence [tex]\(12, 16, 20, 24, 28, \ldots\)[/tex], let's break down the problem step-by-step:
1. Identify the First Term:
The first term of the sequence is given as [tex]\(a_1 = 12\)[/tex].
2. Determine the Common Difference:
To find the common difference ([tex]\(d\)[/tex]), we need to subtract the first term from the second term.
[tex]\[ d = a_2 - a_1 = 16 - 12 = 4 \][/tex]
This indicates that 4 is added to each term to get the next term in the sequence.
3. Formulate the Recursive Formula:
The recursive formula for an arithmetic sequence takes the form:
[tex]\[ a_n = a_{n-1} + d \][/tex]
Given that the first term [tex]\(a_1 = 12\)[/tex] and the common difference [tex]\(d = 4\)[/tex], we can write the recursive formula as follows:
[tex]\[ \left\{\begin{array}{l} a_1 = 12 \\ a_n = a_{n-1} + 4 \end{array}\right. \][/tex]
4. Match with Given Options:
Compare the derived formula with the provided options:
- A. [tex]\( \left\{\begin{array}{l}a_1=4 \\ a_n=a_{n-1}+12\end{array}\right. \)[/tex]: This option has an incorrect first term and common difference.
- B. [tex]\( \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}+4\end{array}\right. \)[/tex]: This matches exactly with our derived formula.
- C. [tex]\( \left\{\begin{array}{l}a_1=32 \\ a_n=a_{n-1}+4\end{array}\right. \)[/tex]: This option has an incorrect first term.
- D. [tex]\( \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}-4\end{array}\right. \)[/tex]: This option has an incorrect common difference.
Hence, the correct recursive formula for the sequence is:
[tex]\[ \text{B.} \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}+4\end{array}\right. \][/tex]
1. Identify the First Term:
The first term of the sequence is given as [tex]\(a_1 = 12\)[/tex].
2. Determine the Common Difference:
To find the common difference ([tex]\(d\)[/tex]), we need to subtract the first term from the second term.
[tex]\[ d = a_2 - a_1 = 16 - 12 = 4 \][/tex]
This indicates that 4 is added to each term to get the next term in the sequence.
3. Formulate the Recursive Formula:
The recursive formula for an arithmetic sequence takes the form:
[tex]\[ a_n = a_{n-1} + d \][/tex]
Given that the first term [tex]\(a_1 = 12\)[/tex] and the common difference [tex]\(d = 4\)[/tex], we can write the recursive formula as follows:
[tex]\[ \left\{\begin{array}{l} a_1 = 12 \\ a_n = a_{n-1} + 4 \end{array}\right. \][/tex]
4. Match with Given Options:
Compare the derived formula with the provided options:
- A. [tex]\( \left\{\begin{array}{l}a_1=4 \\ a_n=a_{n-1}+12\end{array}\right. \)[/tex]: This option has an incorrect first term and common difference.
- B. [tex]\( \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}+4\end{array}\right. \)[/tex]: This matches exactly with our derived formula.
- C. [tex]\( \left\{\begin{array}{l}a_1=32 \\ a_n=a_{n-1}+4\end{array}\right. \)[/tex]: This option has an incorrect first term.
- D. [tex]\( \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}-4\end{array}\right. \)[/tex]: This option has an incorrect common difference.
Hence, the correct recursive formula for the sequence is:
[tex]\[ \text{B.} \left\{\begin{array}{l}a_1=12 \\ a_n=a_{n-1}+4\end{array}\right. \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.